ANALISIS METABOLIT SEKUNDER DAN ANTIBAKTERIDAUN SINTRONG (Crassocephalum crepidioides (Benth.) S. Moore) TERHADAPEscherichia coli - Reni - Yunus; Nurhayu Malik (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Sintrong plant (Crassocephalum crepidioides (Benth.) S. Moore) have potential antibacterial. This study aims to determine metabolite seconder and antibacterial activity of Sintrong leaf extract (Crassocephalum crepidioides (Benth.) S. Moore) from Wawonggole village, Konawe District, Southeast Sulawesi. The Method of research is experimental research. Analysis to determine flavonoids and tannins is extracted with the maceration method, extracted using 96% ethanol. The flavonoids were tested quantitatively using A1C13 10%. The values obtained in determining the levels of flavonoids were 6.751 mg/g of quercetin and tannin 0.43 %. Antibacterial test to Escherichia coli results in concentrations of 5%, 10%, 20%, and 30% the inhibitory power of 12.20 mm, 12.675 mm, 19.15 mm and 20,85, respectively. The Most effective inhibitory of Sintrong leaf extract was the 30 % concentration.